2019
DOI: 10.1002/jcb.28836
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol on the radiosensitivity of 5‐FU in human breast cancer MCF‐7 cells

Abstract: The aim of this study was to assess the efficacy of resveratrol (Res) on radiosensitivity of 5‐fluorouracil (5‐FU) in the spheroid culture of MCF‐7 breast cancer cell line using colony formation examination. Spheroids on day 9 with 300 µm diameters were treated with 20 µM resveratrol and/or 1 µM 5‐FU for one volume doubling time (VDT) (42 hours) and then irradiated with 2 Gy gamma radiation (60Co) in various groups. Then the viability of the cells and clonogenic ability were acquired by blue dye exclusion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Previous studies have indicated the beneficial effects of sirtuins as the best small molecule that activate sirtuins, which extended lifespan in a yeast model [104][105][106][107][108][109]. Although only the longevity extension effect of resveratrol has been reported in C. elegans and D. melanogaster, many subsequent studies reported that resveratrol intake promotes health and plays a preventive role in age-related diseases, such as cancer [110][111][112][113], atherosclerosis [114,115], arthritis [116,117], cataract [118][119][120], cardiovascular disease [121], hypertension [122,123], type 2 diabetes [124][125][126][127], osteoporosis [128][129][130], and Alzheimer disease [131][132][133]. In clinical studies, resveratrol intake improved the memory capacity of elderly individuals and reduced blood lipid levels in obese and type 2 diabetic patients [134,135].…”
Section: Resveratrolmentioning
confidence: 99%
“…Previous studies have indicated the beneficial effects of sirtuins as the best small molecule that activate sirtuins, which extended lifespan in a yeast model [104][105][106][107][108][109]. Although only the longevity extension effect of resveratrol has been reported in C. elegans and D. melanogaster, many subsequent studies reported that resveratrol intake promotes health and plays a preventive role in age-related diseases, such as cancer [110][111][112][113], atherosclerosis [114,115], arthritis [116,117], cataract [118][119][120], cardiovascular disease [121], hypertension [122,123], type 2 diabetes [124][125][126][127], osteoporosis [128][129][130], and Alzheimer disease [131][132][133]. In clinical studies, resveratrol intake improved the memory capacity of elderly individuals and reduced blood lipid levels in obese and type 2 diabetic patients [134,135].…”
Section: Resveratrolmentioning
confidence: 99%
“…Chemotherapy and radiotherapy can complement each other and exert synergistic action on treatment of tumor because RT is significant on local control while chemotherapy is particularly important to systemic metastasis [12,13] . However, the normal tissues couldn't be spared totally when chemo-therapeutic drugs destroying tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…A newly study found that RESV can increase the radiosensitivity of 5-fluorouracil (5-FU), which was used with X-ray to MCF-7 breast cancer cell spheroids. [38] 2.1.2. Quercetin QUER is a type of pentahydroxyflavone, owning five hydroxyl groups placed at the 3-,3′-,4′-,5-and 7-positions.…”
Section: Resveratrolmentioning
confidence: 99%